2015
DOI: 10.1111/jam.12983
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of Microcystis abundance and diversity in determining microcystin dynamics in Lake Erie coastal wetland and downstream beach water

Abstract: This study enriches our understanding of Microcystis population and microcystin ecology in a western Lake Erie coastal wetland and downstream beach water. Our illustrative model brings a new perspective for understanding the ecological relationship between Microcystis population size and structure and MCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 32 publications
0
13
0
2
Order By: Relevance
“…MCs were extracted from Microcystis aeruginosa (identified by targeting PC-IGS and mcyA genes [38]) that was isolated from Lake Erie. M. aeruginosa was cultured in CT medium [39] using sonication (three cycles of 5-min sonication followed by 10-min rest) with a Sonic Dismembrator (50 watts, Fisher Scientific Model F50 with Probe, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…MCs were extracted from Microcystis aeruginosa (identified by targeting PC-IGS and mcyA genes [38]) that was isolated from Lake Erie. M. aeruginosa was cultured in CT medium [39] using sonication (three cycles of 5-min sonication followed by 10-min rest) with a Sonic Dismembrator (50 watts, Fisher Scientific Model F50 with Probe, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Freshwater bacteria have been extensively investigated via culture-independent methods, such as fluorescence in situ hybridization (FISH) method (Sekar et al, 2003; Lindström et al, 2005). Terminal restriction fragment length polymorphism (T-RFLP) and quantitative polymerase chain reaction (qPCR) (Eiler and Bertilsson, 2004, 2007; Hu et al, 2016) were used for studying diversity of freshwater bacterial communities associated with cyanobacterial bloom. The application of culture-independent methods provided information on bacterial diversity in freshwaters that had been underestimated in the past.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, Rinta-Kanto and Wilhelm (2006) studied the genetic diversity of potentially toxic Microcystis based on the McyA amino acid sequence and reported new sequences of the mcyA gene (Rinta-Kanto and Wilhelm, 2006). Using mcyA amplification and denaturing gradient gel electrophoresis (DGGE), Hu et al (2016) found that the microcystin variants were related to the band pattern obtained, implying that the composition of Microcystis community determined the kind of microcystin produced (Hu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A study in Lake Erie (USA) found that relative abundances of some genotypes changed temporally, indicating the existence of different genotypes adapted to particular environmental characteristics (Hu et al, 2016). In the same ecosystem, Berry et al (2017) analysed Microcystis oligotypes using a computational method (oligotyping) based on the V4 region of the 16S rRNA gene and found changes in Microcystis oligotypes composition related to spatial nutrient gradients.…”
Section: Discussionmentioning
confidence: 99%